"INRI CRISTO" E SEUS DISCÍPULOS: UM ESTUDO SOCIOLÓGICO DAS MOTIVAÇÕES NA ADESÃO AO MOVIMENTO MESSIÂNICO - Martins, Edson (2006)
This thesis is a sociological analysis of the main motivations that made men and women let go of everything they were doing up to a certain moment and follow a messianic leader known as Inri Cristo, who claims to be the reincarnation of Jesus Christ. It shows, at first, a brief historical account of the three most important and thoroughly documented Brazilian messianic movements: Canudos, Juazeiro and Contestado, so as to understand the context in which such movements were brought up. This account enables the making of comparisons between these three movements and the Inri Cristo one. The research presents and analyses the appearance of the messiah, the content of his message, and the structure of his church, localized in a popular district of Curitiba. After that, there will be an analysis of the data about his disciples, which was gathered in a field research. This analysis will make it possible to understand who they are, their everyday living within the community, the way they absorb the official discourses and how they pass them on, and, most important, which the main motivations are that made them follow the messianic leader. There is also a comparative analysis between the disciples of Inri Cristo and the followers of the movements mentioned above, so as to establish convergent and divergent aspects between them. Finally, there is a presentation of the innovations brought by this messianic movement and its contributions for the study of Brazilian messianic movements.